The influence of barriers on entrepreneurial intentions: Student entrepreneurship in Western Balkan countries - Milenko Matić; Bojan Leković; Dušan Bobera (Anali Ekonomskog fakulteta u Subotici, 2023)
The paper is based on the findings of the research of students of business administration in the countries of the Western Balkans and aims to identify the impact of entrepreneurial barriers on their intentions to start entrepreneurial ventures. Barriers are classified into four categories. The first category is knowledge and skill barriers. The second group of barriers includes financial barriers. Subjective circumstances represent the third, and administrative procedures and fiscal burdens are the fourth groups of barriers. The research was conducted with 910 respondents, which consists of 71 questions. For the analysis, 6 questions related to the demographic profile and general information were used, while for the second part, 14 were used, which belong to the categories of barriers. The SPSS program was used for the empirical analysis of the results. The results showed that financial barriers, administrative procedures, and fiscal burdens harm entrepreneurial intentions. Within the group of barriers of knowledge and skills, the lack of business plan development skills and the lack of financial skills harm entrepreneurial aspirations, while the other barriers are not statistically significant. It was confirmed that statistically significant barriers to entrepreneurial intentions belong to subjective circumstances: lack of support from the environment and fear of failure.